IDENTIFIKASI TEKNIK MENANGKAP IKAN BERDASARKAN ENTHESOPATHIES PADA RANGKA MANUSIA DARI SITUS GILIMANUK, BALI - Dicky Caesario Wibowo (Berkala Arkeologi, 2019)
Abstract Due to its location in Gilimanuk Bay and its findings, Gilimanuk site stated for having fishers as subsistence strategy. This research uses pathological condition called enthesopathies as the primary data to induce fishing techniques as part of their daily activities. Identification enthesopathies follows procedure proposed by Hawkey & Merbs and Mariotti. Result shows only two specific techniques which can be identified through pathological condition. Those techniques are fishing with stick and spearing methods. Based on pathological conditions, early fisher’s community from Gilimanuk only developed shallow water fishing techniques. Absence of other fishing techniques indicates by artefacts and induced from enthesopathies might lead to early assumption about natural resources are widely available and easy to procure in surrounds environment.